Treating extravasation injuries in infants and young children: a scoping review and survey of UK NHS practice - Mark Corbett; David Marshall; Melissa Harden; Sam Oddie; Robert Phillips; William McGuire (BMC, 2019)
Abstract Background Extravasation injuries are caused by unintended leakages of fluids or medicines from intravenous lines but there is no consensus on the best treatment approaches, particularly in infants and young children. Methods This paper presents a more succinct account of a study of treatments for extravasation injuries in infants and children which has also been reported in full as an NIHR HTA report. A systematic scoping review and survey of UK NHS practice were undertaken. Twelve databases - including MEDLINE and EMBASE - were searched for relevant studies in February 2017. Studies of children with extravasation injuries receiving any treatment for extravasation injury were eligible, providing they reported one of the following outcomes: wound healing time, infection, pain, scarring, functional impairment, and requirement for surgery. Studies were screened in duplicate. Data were extracted by one researcher and checked by another. Studies were summarised narratively. An online questionnaire was distributed to NHS staff at neonatal units, paediatric intensive care units and principal oncology/haematology units. Results The evidence identified in the scoping review was mostly comprised of small, retrospective, uncontrolled group studies or case reports. The studies covered a wide range of interventions including conservative management approaches, saline flush-out techniques (with or without prior hyaluronidase), hyaluronidase without flush-out, artificial skin treatments, debridement and plastic surgery. Few studies graded injury severity and the results sections and outcomes reported in most studies were limited. There was heterogeneity across study populations in many factors. The survey yielded 63 responses from hospital units across the UK. Results indicated that although most units had written documentation for treating extravasation injuries, only one-third of documents included a system for grading injury severity. The most frequently used interventions were elevation of the affected area and analgesics. Saline wash-out treatments, either with or without hyaluronidase, were regularly used in about half of all neonatal units. Most responders thought a randomised controlled trial might be a viable future research design. Conclusions There is some uncertainty about which are most the promising treatments for extravasation injuries in infants and young children. Saline flush-out techniques and conservative management approaches are commonly used and may be suitable for evaluation in trials. Although conventional randomised trials may be difficult to perform a randomised registry trial may be an appropriate alternative design.